A Clustering Approach for Information Retrieval Using A Quantum-Based Computation Technique - Bhagawati, Rupam; Subramanian, Thiruselvan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Today’s era of the internet and digitalization requires information of various forms. Information in any configuration is predominant in performing various tasks like management and retrieval. Static information is mostly present in documents and to perform retrieval, browsing, and managing this kind of information, we have many strategies available in classical form. Many classical forms can also be categorized from high level to low level. To some extent, the realm of Quantum Computing is also employed for the task and many contemporary researchers state efficient algorithms for the task. Relevant information per the user’s need is the most prominent goal of an Information System. Documents play an important role in information in this regard as well as keeping uncertainty on the relevancy of correct information as per the requirement. Documents are representations of all kinds of information related to numerous fields like academia, media, law, engineering, geography, and many more. A huge collection of information representation is scattered everywhere throughout the logical world of the internet. The collection is a blender of all types of documents from different fields and semantics. Searching and sorting complete relevant documents from this gigantic blender according to information need is an onerous task to an extent. Grouping the same information in clusters brings a change to the relevancy rate of the required information. Quantum mechanics track towards Quantum information processing provides a realm for clustering of information in the form of acquaintances. Using quantum computation in the realm of quantum mechanics, an algorithm is proposed for the task which will lead to the grouping of information by considering the microscopic properties of each and every acquaintance.